A PHENOMENOLOGICAL STUDY OF ENGLISH TEACHERS’ REFLECTION ON THEIR CHALLENGES AND INSTRUCTIONAL MANAGEMENT IN PATTANI PROVINCE IN THAILAND - Thongmak, Sirikarn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
This phenomenological study aimed to explore and critically report the challenges and limitations which influence the instructional management of five English teachers in Pattani province, the southern border of Thailand. The participants of the study were five English teachers working in a primary school in Pattani province. This qualitative analysis was conducted based on the semi-structured interview. Their personal life experiences, challenges they faced, and instructional management were revealed and then discussed in detail. The findings indicated that there were certain challenges and instructional management developed by the teachers to address the educational situation. Furthermore, the teachers’ needs were obviously in terms of security, effective teaching methodology, as well as material development to practically serve their local circumstances.